The Politeness Strategy in Compliment in Pursuit of Happiness Movie - Trifani, Evanka; Rohana, Yogi (IREELL: Indonesian Review of English Education, Linguistics, and Literature, 2023)
Politeness Strategies is one of topic discussed in pragmatics. The politeness principle is a set of maxims that describe the way in which politeness operates in a conversational exchange. This study focused on compliments and the responses. The theory of politeness strategies can be applied into media entertainment such as in a movie. This study examined the types of Politeness strategies in compliments and the responses in The Pursuits of Happyness movie that uttered by all characters and the types that frequently appears in the movie. This study was conducted by using descriptive qualitative method as the data were derived from the movie script of The Pursuits of Happyness by downloading from the internet. The result shows that there are 19 data of compliments and 5 data of compliment response. There are 9 data categorized into generosity maxim type, 3 data categorized into modesty maxim type, 3 data categorized into sympathy maxim type, 2 data categorized into agreement maxim type, and 2 data of approbation maxim. It can be concluded that generosity is the most frequently used by the characters in The Pursuits of Happyness movie. The use of those findings in education will explore the theory of politeness strategies that are learned by EFL English to develop their ability to succeed in academic or social communication and it becomes a value-added treasure of scientific knowledge in the field of education in linguistics.